Scrittura come visione - Vecce, Carlo (Romanica Silesiana)
At the beginning of a creative process, a literary text needs always to pass the step that ancient writers called ‘inventio’. In the ‘inventio’, of course, human mind looks more for visual images than for abstract ideas. Fantasy and imagination, by this way, are non very far from the world of dreams, made basically by images and sensations. During this first step, some writers can use words and language just to ‘describe’ images and visions. Among modern italian witers, we could assume the important witness of Italo Calvino, in Lezioni americane. But other interesting examples are to be found also in texts by Iacopone da Todi, Dante, Petrarca, Leonardo da Vinci and Dino Campana. What is important (Calvino says in Lezioni americane), it is to continue to recognize to the literature a significant role in the education of imagination. Imagination is foundation to thinking, and could be menaced today by modern media-society. Key words: Italo Calvino, literature, fantasy, imagination.